A wavelet-based OFDM system implemetation on GNURadio platform vs. an FFT-based (2021)
This paper deals with the implementation of an OFDM system which uses wavelets as the carriers through the Discrete Wavelet Transform. It analyzes performance in terms of the Bit Error Rate (BER) for different values of signal-to-noise ratio in an Additive White Gaussian Noise (AWGN) wireless transmission environment. Additionally, it simulates the BER response for different bandwidths in the wavelet-based system, in order to reduce it, lessening it’s BER performance until it equals the FFT-based, thus we achieved an improvement in spectral effieciency. To ensure the same testing conditions, both systems were implemented using the open source GnuRadio Software-Defined Radio (SDR) platform.